Impact of Air Jet Impingement Technology on the Strength of Tissue Paper - Mariusz Reczulski; Piotr Pospiech; Kinga Troszczyńska; Maria Bieńkowska (BioResources, 2024)
Impinging air jets can be used to dewater, heat, and dry the web of tissue paper. High velocities of the air jets degrade the paper, and appropriate adjustments to the jet velocity and the distance of the nozzle from the surface of the wet web are crucial to obtain the highest quality product. This work investigated the correlation between the velocity of the air jet and the strength of paper subjected to the impingement method. Papers with an initial moisture content of 20% and various pulp mixes were tested, and the physical properties of papers were explored. After impinging an air jet, different tensile strength limits were obtained in the machine and cross directions. The paper had lower apparent density and higher roughness compared to classical pressing. The dependence of tensile strength and roughness on the fibers composition also was determined. Increasing the amount of eucalyptus fibers in impingement dewatered paper resulted in a decrease in its tensile strength and roughness. The value of elongation before breaking was the highest for softwood papers after the impingement method. The maximum velocity of an air jet that can be used to dewater or dry paper without the risk of damage to the papers was determined.